PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR-SHARE TERHADAP HASIL BELAJAR FISIKA MATERI POKOK HUKUM II NEWTON SISWA SMP NEGERI SIABU - Siregar, Dwi Aninditya (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2022)
The aim of this research was to know whether there was a significant influence of using cooperative learning model of Think Pair-Share type on student’s achievement in Newton’s Law II subject at the eighth grade students of SMP Negeri 1 Siabu. The population of this research was all the eighth grade students of SMP Neger 1 Siabu. They were 232 students. Sampel was taken by using cluster technique sampling. The writer took VIII-5 which include 40 students. The research used experimental method. In collecting the data, the writer used test and observation. The data was analyzed two ways, descriptive analysis and inferential statistics. Based on descriptive analysis, students’ achievement in Newton’s Law II subject before using cooperative learning model of Think Pair-Share type was 60,50. It was categorized “enough” While the students’ achievement in Newton’s Law II subject after using l cooperative learning model of Think Pair-Share type was 80,50. It was categorized